2017
DOI: 10.1063/1.5009744
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport through a junction entirely consisting of molecules from first principles

Abstract: Using first-principles calculations based on density functional theory combined with the nonequilibrium Green's function formalism, we studied the spin transport through a single molecular junction which consists of a single 1,4-benzenedithiolate (BDT) molecule and two ferromagnetic electrodes [(Ge5)Fe]∞. A large magnetoresistance ratio (MR) of 21100% was found in the [(Ge5)Fe]∞-BDT-[(Ge5)Fe]∞ molecular junction at small bias voltage, and the MR value decreased with the increase in the applied bias voltage. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…According to the previous theoretical studies, T ↑ ( E F ) and T ↓ ( E F ) of mirror‐symmetric devices are consistent in APC state, which shows a zero SIE. [ 54,55 ] Here, SIE in APC state is not zero since R,S‐MET molecules are not mirror‐symmetric.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous theoretical studies, T ↑ ( E F ) and T ↓ ( E F ) of mirror‐symmetric devices are consistent in APC state, which shows a zero SIE. [ 54,55 ] Here, SIE in APC state is not zero since R,S‐MET molecules are not mirror‐symmetric.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent calculations on [(Ge 5 )Fe] ∞ -BDT-[(Ge 5 )-Fe] ∞ molecular junctions showed that the highest MR ratio can reach 21100%. 52 However, a highly spin-polarized current is lacking when the magnetization configuration changes. The OMTJs present here show that, in addition to the extremely large TMR value, a perfect spin-filter effect can be obtained independent of the contact geometry and magnetization configuration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…From an applicable point of view, more comprehensive studies such as the effects of structural defects and surface disorder are necessary in future work. Furthermore, recent calculations on [(Ge 5 )­Fe] ∞ -BDT-[(Ge 5 )­Fe] ∞ molecular junctions showed that the highest MR ratio can reach 21100% . However, a highly spin-polarized current is lacking when the magnetization configuration changes.…”
Section: Resultsmentioning
confidence: 99%
“…We used 3 × 3 × 1 k -point grids in the Brillouin zone (BZ) for structural calculations and denser 5 × 5 × 1 k -point grids for density of states calculations. Transport properties were calculated by the non-equilibrium Green’s function method with density functional theory (NEGF-DFT) performed in the Nanodcal package. , The double-zeta polarized (DZP) atomic orbital basis set and the local density approximation functional were used in the transport calculations. , The k -points of 5 × 5 × 1 were used in the transport calculations. The NEGF-DFT self-consistent calculation was performed until the Hamiltonian was converged to 10 –4 eV.…”
Section: Methodsmentioning
confidence: 99%
“…40,41 The double-zeta polarized (DZP) atomic orbital basis set and the local density approximation functional were used in the transport calculations. 42,43 The k-points of 5 × 5 × 1 were used in the transport calculations. The NEGF-DFT selfconsistent calculation was performed until the Hamiltonian was converged to 10 −4 eV.…”
Section: Methodsmentioning
confidence: 99%